STAKEHOLDER PRESSURE MODERATES INDUSTRY TYPE AND EDUCATION BACKGROUND OF THE BOARD ON SUSTAINABILITY REPORTING - Widya Ningsih; Nofryanti; Iin Rosini (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
The purpose this research is to obtain empirical evidence regarding Stakeholder Pressure Moderating Industry Type and Educational Background of the Board on Sustainability Reporting. This research used a purposive sampling method in determining the sample with 33 companies as samples and a 5 year observation period from 2018 to 2022 so that 165 observation data were obtained. Research data was obtained through the official website of the Indonesian stock exchange and the websites of each company. Data analysis used E-Views 10 with Common Effect Model panel data regression analysis. The results of the research show that Industry Type has a negative effect on Sustainability Reporting, Educational Background of the Board has no effect on Sustainability Reporting, Stakeholder Pressure moderates the relationship between Industry Type and Sustainability Reporting, and Stakeholder Pressure moderate the relationship between Educational Background of The Board and Sustainability Reporting.